Pandemic as Opportunity - Judy MacLeod Reardon; Carey Huddlestun; Karen Doster-Greenleaf (Journal of New Librarianship, 2021)
The COVID-19 pandemic presented the Kennesaw State University Library System with the question, " How can the library maintain live face-to-face reference services in a manner that is safe for all involved ?" Challenges to creating a live virtual reference desk that arose included the need to serve two campuses simultaneously, librarians working from home, and using conferencing technology in unexplored ways. The resulting Virtual In-Person (VIP) Reference service was the answer to our immediate situation, yet lessons were learned for future opportunities to push our services beyond the traditional.